Persistent negative temperature response of mesophyll conductance in red raspberry (Rubus idaeus L.) leaves under both high and low vapour pressure deficits: a role for abscisic acid?. (September 2017) - Qiu, Changpeng; Ethier, Gilbert; Pepin, Steeve; Dubé, Pascal; Desjardins, Yves; Gosselin, André
Abstract: The temperature dependence of mesophyll conductance ( g m ) was measured in well‐watered red raspberry ( Rubus idaeus L.) plants acclimated to leaf‐to‐air vapour pressure deficit (VPDL) daytime differentials of contrasting amplitude, keeping a fixed diurnal leaf temperature ( T leaf ) rise from 20 to 35 °C. Contrary to the great majority of g m temperature responses published to date, we found a pronounced reduction of g m with increasing T leaf irrespective of leaf chamber O2 level and diurnal VPDL regime. Leaf hydraulic conductance was greatly enhanced during the warmer afternoon periods under both low (0.75 to 1.5 kPa) and high (0.75 to 3.5 kPa) diurnal VPDL regimes, unlike stomatal conductance ( g s ), which decreased in the afternoon. Consequently, the leaf water status remained largely isohydric throughout the day, and therefore cannot be evoked to explain the diurnal decrease of g m . However, the concerted diurnal reductions of g m and g s were well correlated with increases in leaf abscisic acid (ABA) content, thus suggesting that ABA can induce a significant depression of g m under favourable leaf water status. Our results challenge the view that the temperature dependence of g m can be explained solely from dynamic leaf anatomical adjustments and/or from the known thermodynamic properties of aqueous solutions and lipid membranes.​ Abstract : The temperature dependence of mesophyll conductance ( g m ) was investigated under ambient atmosphere versus under non‐photorespiratory conditions in well‐watered raspberry plants acclimated to diurnal VPDleaf differentials of contrasting amplitude. Contrary to the great majority of g m temperature responses published to date, we found a pronounced reduction of g m with increasing leaf temperature ( T leaf ) between 20 and 35 °C irrespective of leaf chamber O2 level and of the VPDleaf regime under which the plants had been acclimated and subsequently measured. The concerted diurnal reductions of g m and stomatal conductance contrasted with the diurnal increases in leaf hydraulic conductance, but were well correlated with increases in leaf abscisic acid (ABA) content, thus adding to the recent evidence suggesting that ABA can induce a significant depression of g m under favourable leaf water status. To our knowledge, this is the first time that dynamic changes in foliar ABA levels in response to diurnal fluctuations in T leaf /VPDleaf are shown to be a major determinant of the temperature dependence of g m .